History of UiTM / Yonina Sikim and Nichole Heather Esak - Sikim, Yonina; Esak, Nichole Heather (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
UiTM Samarahan Campus is one of the three campuses of Universiti Teknologi MARA Sarawak Branch. The campus may be found in Kota Samarahan, which is situated approximately 20 kilometres away from Kuching City. The Samarahan campus of the Universiti Teknologi MARA is the institution's second branch campus, and it can be found in the Malaysian state of Sarawak. Approximately around 1973 or 1974, this campus was created in the Batu Lintang neighbourhood of Kuching. The Agricultural Training Institute at Semenggok in Sarawak became the new home of the ITM Sarawak Campus in 1987 and remained there until 1989. Following its time in Semenggok, the campus then moved to Samariang, where it remained until 1997. Since it first opened in 1997, the campus has always been located in the same location which is in Kota Samarahan. The third campus in Mukah started operation in 2002. UiTM Sarawak marked the opening of its second campus in Kota Samarahan in the year 2013. Each of these campuses is dedicated to its very own Perpustakaan Tun Abdul Razak, which was initially formed in 2013.